A Study on the Recruitment and Selection practices of IT-ITES firms in India - Sethi, Deepti (2005)
The need to attract and select a highly skilled and a competent global workforce in a tight and competitive labour market characterized by a skills shortage and limited suitability of manpower has necessitated the adoption of best practices in recruitment and selection by firms in the IT-ITES industry in India. This study examines the recruitment and selection practices of IT-ITES firms in India and attempts to validate and extend the findings of studies in recruitment and selection conducted in Western countries to a non-Western context.